PENGARUH ASSET TANGIBILITY, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Graciella, Meggan; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to provide empirical evidence on the impact of asset tangibility, profitability, growth and liquidity on the capital structure in manufacturing industry companies listed in Indonesian Stock Exchange during the period of 2018-2020. In this research, samples used of 74 manufacturing companies for three years were selected previously using the purposive sampling mtehod. Secondary Data were used in this research which is in the form of financial information from financial statement. Data was processed by eviews 12. The results of this study shows that asset tangibility, profitability, and growth have a significant effect on capital structure. Suggestion that can be given for next research it is expected to use other independent variables such as company size, non-debt tax shield, company age that might show better result.